Recent Developments in Self-microemulsifying Drug Delivery System: An Overview - Kaushik, Deepak (Asian Journal of Pharmaceutics (AJP), 2019)
Self-microemulsifying drug delivery system (SMEDDS) has emerged as a distinctive approach for the improvement of low bioavailability, high intra- and inter-subject changeability, and absence of dose proportionality difficulties associated with hydrophobic (water-repelling) drugs due to their incomparable potentials. SMEDDS is isotropic mixture of drug, surfactants, cosurfactants, and oil which have unique ability to form fine o/w microemulsion on slight shaking followed by dilution with fluid, such as gastrointestinal fluid. In vitro features such as concentration of surfactants, ratio of oil to surfactant, polarity of emulsion, zeta potential, and size of droplet play a vital role in drug absorption orally. It would be more accurate to say that it disperses out of oily droplets into gastrointestinal tract media, resulting in the development of equilibrium among outer dispersed media and the drugs dissolved in oily droplets in spite of saying that the drug is released from SMEDDS. This analysis is useful for the better understanding of SMEDDS for its recent advancements with an emphasis on absorption pathway of lipids, patents, and research work. The present article provides a discussion on recent developments such as self-microemulsifying mouth dissolving film, supersaturable, herbal, and sponges carrying SMEDDS.